The effect of neuromuscular training on kinetic variables in male athletes with trunk control defects - Behnam Moradi; Amir Letafatkar; Malihe Hadadnezhad; Mahdi Hosseinzadeh; Mahdi Khaleghi (Sport Sciences and Health Research)
Background: Trunk control defect is one of the neuromuscular defects that can cause sports-related injuries in athletes.Aim: This research investigated whether neuromuscular training affects several kinetic parameters in male athletes who had trouble controlling their trunks during a change-of-direction movement.Materials and Methods: The present study used a pre-test-post-test design and was conducted semi-experimentally. Purposefully chosen male athletes (n= 29) with trunk control defects were randomly divided into two groups: control (n= 14) and experiment (n= 15). A Kistler force plate was used to quantify kinetic variables. The exercises were performed for 6 weeks, 3 sessions per week (30 min each session). To analyze the data, dependent t-test and analysis of covariance and SPSS software version 21 were used at the significance level of P<0.05.Results: The findings indicated a significant decrease in the time to peak anterior-posterior force (P=0.010), time to peak mediolateral force (P=0.001), time to peak vertical force (P=0.003), and rate of loading (P=0.001) of the experimental group. The differences in all control group variables were insignificant, P>0.05.Conclusion: Performing neuromuscular training is likely to improve the direction change mechanism and prevent injury in athletes with trunk control defects.